St. Louis Paper - Efficiency in Use of Oil as Fuel (with Discussion) - W. N. Best (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1921)
This paper is not intended as a scientific discussion of the combustion of oil but is written from the standpoint of an operator who has the experience and qualifications necessary to guide others in producing the most economical results in the use of liquid fuels. Oil, in this paper, usually means petroleum or its products but incidental reference is made to other liquid and gaseous fuels, so that the term may be considered as referring to all liquid and gaseous hydrocarbons in comparison with solid fuels, as coal and wood. However, only a few of the principal factors in the use of oil as a fuel can be given. The present, and prospective, high price of coal is causing users of fuel to renew inquiry as to the merits of other forms of fuel for industrial purposes. Crude oil (petroleum) is proving to be one of the world's most valuable mineral resources. The recent discovery that oil underlies a considerable area of the United States, Mexico, and other parts of the world to a greater extent than was formerly believed and the large production of some of the wells in these areas shows the probable quantity of fuel oil that may now be available. Through the energy of Lord Cowdrey, who was one of the pioneers of the oil industry in Mexico, oil has been discovered in England; some prominent geologists believe that it may be found in quantity in Great Britain. For years, oil has been known to be of great value in the manufneture of metals. It has proved incomparable in forge shops, steel foundries, heat-treating furnaces, and wherever accuracy of temperatures is essential, or where a maximum output is desired as well as quality of metal. In some types of equipment, the output produced with oil as fuel is double that obtained with coal and at a reduction of 50 per cent. in the cost of the fuel. For example, in drop-forging plants, the metal is always waiting for the man when oil is used as fuel, whereas with coal, the man must wait for the metal to become sufficiently heated. It has only been since January, 1919, that the oil supply could be relied on for boiler service, owing to the war conditions and the inability to get oil tankers for the delivery of the oil from Mexico to Atlantic ports; but now a constant supply is assured, and many manufacturers are installing it in their power plants. The cost varies with the size of the